2021
DOI: 10.17582/journal.aavs/2021/9.5.743.753
|View full text |Cite
|
Sign up to set email alerts
|

Usage of Some Natural or Synthetic Compounds as Antioxidant and their Effects on Cryopreservation and Penetration of Ram Spermatozoa

Abstract: T he chilling of semen has some adverse effects on sperm properties. Modifying dilators with traditional and untraditional refrigerants can influence sperm properties (Mohamed et al., 2020). Preservation of semen alters sperm structure and biochemical properties and impedes fertilization (Mohamed et al., 2019).The addition of antioxidants to semen diluents could be extended storage time, improve motility, decrease cellu-lar damage, protected acrosomal membrane and raise the viability and fertilization ability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Bezerra et al (2022) discovered that a 12.5 μg/mL concentration of rosemary extract increased sperm motility, improved membrane integrity at 25 μg/mL, and enhanced acrosome integrity at 6.25 μg/mL after thawing. Moreover, Diab et al (2021) demonstrated that the use of 20 mg of rosemary extract in the ram semen extender at 37 and 5°C improved motility, live sperm count, and reduced abnormality rates. This improvement in semen quality might be associated with the ability of herbs to enhance the antioxidant defence system and reduce the synthesis of OS in sperm.…”
Section: Non‐enzymatic Antioxidantmentioning
confidence: 99%
“…Bezerra et al (2022) discovered that a 12.5 μg/mL concentration of rosemary extract increased sperm motility, improved membrane integrity at 25 μg/mL, and enhanced acrosome integrity at 6.25 μg/mL after thawing. Moreover, Diab et al (2021) demonstrated that the use of 20 mg of rosemary extract in the ram semen extender at 37 and 5°C improved motility, live sperm count, and reduced abnormality rates. This improvement in semen quality might be associated with the ability of herbs to enhance the antioxidant defence system and reduce the synthesis of OS in sperm.…”
Section: Non‐enzymatic Antioxidantmentioning
confidence: 99%